Routing multiple vehicles in Singapore - Soh, Teck Seng (2015)
Modern day cities face the common issue of over congested roads, an issue brought about from the influx of population and wealth, which results in a greater number of cars on the road. The project will simulate the traffic situation in Singapore and apply some traffic policies. The results of these policies will then be analyzed to determine if they are suitable for alleviating traffic jams. The first policy routes a certain fraction of all vehicles away from highways in an attempt to reduce highway congestion. The second policy builds on the first, but instead of selecting the fraction randomly, cars are picked based on their travelling distance. The third policy analyses chokepoints and congestion prone areas and attempts to route cars around them. The main software to be used in this project will be SUMO-Simulator, an open source traffic simulator developed by the Institute of Transportation Systems, Germany. Map data will be obtained from OpenStreetMaps.com, and edited using Java OpenStreetMap Editor (JOSM). O/D trips are estimated based on Singapore population data and certain assumptions, and generated using Java. SUMO-Simulator generates two different output files. The first file contains data pertaining to each individual car. The second file contains data for each road edge in the network. These files are then analysed in Excel and converted to graph form to provide better visualisation of data. The data obtained is then used to provide better understanding the effectiveness of these policies, providing better insight as to how they can be used to reduce traffic congestion.